'Although I use science, it's an emotional thing': conservation practitioners' use of positive affect to frame messages about threatened birds. Issue 4 (1st October 2020) - Ainsworth, Gillian Barbara; Burns, Georgette Leah
ABSTRACT: Birds are of significant scientific and public interest yet although human interactions with birds are widespread and diverse in nature, relatively few people participate in conservation initiatives. Understanding how conservation practitioners describe conservation issues and whether this resonates with recipients' attitudes could help create more appealing conservation strategies. This study applied a new typology of 12 avifaunal attitudes during 74 qualitative interviews with Australian conservation practitioners from the government, non-government, private, public and scientific sectors to investigate how they frame threatened bird issues. Messages about threatened bird conservation were typically positive and framed according to four major themes: morality, intrinsic value, empathy and loss. A strong link between empathy for wildlife and moral justification for preventing extinctions emerged. We recommend that public messages advocating for threatened bird conservation could be framed in positive ways that arouse emotions. Expressing a broad range of attitudes could appeal at both public interest and policy-maker levels and assist with developing more effective frames to capture some of the complex social landscape within which threatened species conservation operates. These findings could apply to wildlife conservation in Australia and elsewhere. Finally, the typology can assist with developing appropriately framed and targeted conservation engagement strategies.